China's "Socialist Market Economy": A Systemic Trade Issue - Jacques Pelkmans (Intereconomics, 2018)
The socialist market economy with Chinese characteristics has turned into a systemic trade and investment issue both bilaterally and multilaterally. The hope that WTO membership would eventually transform China into a market economy with distortions that would gradually become tolerable and negotiable has not been borne out.
Keywords: 330; China; Development policy; Protectionism; Tariffs; Trade policy